The p53 pathway induction is not primarily dependent on Ataxia Telangiectasia Mutated (ATM) gene activity after fludarabine treatment in chronic lymphocytic leukemia cells - Navrkalova, Veronika; Sebejova, Ludmila; Zemanova, Jana; Jaskova, Zuzana; Trbusek, Martin (Leukemia & lymphoma, 2013)
The prognostic role of ATM defects is well documented in chronic lymphocytic leukemia. However, the predictive value of ATM inactivation is much less understood, even in response to common drugs like fludarabine. It has been demonstrated that CLL cells having inactive ATM exhibit defective phosphorylation of its downstream targets after fludarabine treatment. We performed alternative analysis focusing on fludarabine-induced p53 accumulation and induction of p53-downstream genes after artificial ATM inhibition and, in parallel, using cells with endogenous ATM inactivation. We show that after 24h fludarabine exposure: (i) 5 out of 8 ATM-deficient samples (63%) normally accumulated p53 protein, and (ii) all analyzed ATM-deficient samples (n = 7) manifested clear induction of p21, PUMA, BAX, and GADD45 genes. In all experiments, doxorubicin was used as a confined ATM inductor and confirmed effective ATM inactivation. In conclusion, CLL cells lacking functional ATM appear to have normal response to fludarabine regarding the p53 pathway activation.
Keywords: nádorový supresorový protein p53; Gene Expression Regulation, Leukemic; proliferační antigen buněčného jádra; signální transdukce; Transcriptional Activation; vidarabin; Vidarabine; ATM protein; Signal Transduction; dvouřetězcové zlomy DNA; Tumor Suppressor Protein p53; Antineoplastic Agents; Proliferating Cell Nuclear Antigen; histony; chronická lymfatická leukemie; Histones; protinádorové látky; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; DNA Breaks, Double-Stranded; aktivace transkripce; Ataxia Telangiectasia Mutated Proteins; regulace genové exprese u leukemie; lidé